Eso-Sponge® for anastomotic leakage after oesophageal resection or perforation: outcomes from a national, prospective multicentre registry. Issue 2 (22nd April 2022) - Richter, Florian; Hendricks, Alexander; Schniewind, Bodo; Hampe, Jochen; Heits, Nils; von Schönfels, Witigo; Reichert, Benedikt; Eberle, Katrin; Ellrichmann, Mark; Baumann, Petra; Egberts, Jan-Hendrik; Becker, Thomas; et al.
Abstract: Background: Anastomotic leakage (AL) after oesophagectomy and oesophageal perforations are associated with significant morbidity and mortality. Minimally invasive endoscopy is often used as first-line treatment, particularly endoluminal vacuum therapy (EVT). The aim was to assess the performance of the first commercially available endoluminal vacuum device (Eso-Sponge®) in the management of AL and perforation of the upper gastrointestinal tract (GIT). Methods: The Eso-Sponge® registry was designed in 2014 as a prospective, observational, national, multicentre registry. Patients were recruited with either AL or perforation within the upper GIT. Data were collected with a standardized form and transferred into a web-based platform. Twenty hospitals were enrolled at the beginning of the study (registration number NCT02662777; http://www.clinicaltrials.gov ). The primary endpoint was successful closure of the oesophageal defect. Results: Eleven out of 20 centres recruited patients. A total of 102 patients were included in this interim analysis; 69 patients with AL and 33 with a perforation were treated by EVT. In the AL group, a closure of 91 per cent was observed and 76 per cent was observed in the perforation group. The occurrence of mediastinitis ( P  = 0.002) and the location of the defect ( P  = 0.008) were identified as significant predictors of defect closure. Conclusions: The Eso-Sponge® registry offers the opportunity to collate data on EVT with a uniform, commercially available product to improve standardization. Our data show that EVT with the Eso-Sponge® is an option for the management of AL and perforation within the upper GIT. Abstract : We present results of 102 patients recruited in a multicentre study assessing the performance of the first commercially available endoluminal vacuum device (Eso-Sponge®) in various indications (anastomotic insufficiency and perforation within the upper gastrointestinal tract). It seems to offer a safe, effective, and minimally invasive therapeutic approach with low mortality.